Implementasi Basis Data Sederhana Menggunakan MySQL/PostgreSQL - Jesika Vinatalia Dachi; Jiyan Suhada (Router : Jurnal Teknik Informatika dan Terapan, 2025)
Databases play an essential role in modern information systems because they enable the efficient storage, management, and retrieval of structured data. This study focuses on the implementation of a simple database using two relational database management systems (RDBMS), namely MySQL and PostgreSQL. The research stages are carried out through requirements analysis, designing entity-relationship diagrams, implementing tables and their relationships, and testing the system to assess functionality. The case study used is student data recording, where both RDBMSs are tested through a series of basic CRUD (Create, Read, Update, Delete) operations. The results show that both MySQL and PostgreSQL are capable of carrying out these operations effectively while maintaining data integrity and consistency. However, PostgreSQL offers additional advantages due to its support for more complex data types, a better level of compliance with SQL standards, and advanced features that support the needs of large-scale application development. Conversely, MySQL remains superior in terms of ease of use and application to simpler needs, making it more practical for small projects or applications with standard workloads. Based on these findings, it can be concluded that both RDBMSs are equally suitable for use, but the ideal choice depends heavily on the context of the needs; PostgreSQL is more suitable for applications that demand high scalability and size, while MySQL remains relevant for lightweight and efficient implementations.